Closed Incision Negative Pressure Therapy Reduces Surgical Site Infections in Vascular Surgery: A Prospective Randomised Trial (AIMS Trial). (September 2018) - Gombert, Alexander; Babilon, Michael; Barbati, Mohammad E.; Keszei, Andras; von Trotha, Klaus T.; Jalaie, Houman; Kalder, Johannes; Kotelis, Drosos; Greiner, Andreas; Langer, Stephan; Jacobs, Michael J.; Grommes, Jochen
Abstract : Background: Surgical site infections (SSIs) of the groin remain a crucial problem in vascular surgery, prompting great interest in preventative techniques, such as closed incision negative pressure therapy (ciNPT). This prospective randomised study aimed to assess the potential benefits of ciNPT application after groin incisions for vascular surgery. Method: The study included 204 patients who underwent vascular surgery for peripheral artery disease (PAD) at two sites between July 2015 and May 2017. These patients received post-operative treatment with ciNPT (intervention group) or standard wound dressings (control group). After exclusion, 188 patients were assessed for SSIs using the Szilagyi classification. Results: The mean patient age was 66.6 ± 9.4 years (range 43–85 years), and 70% were male ( n  = 132). Regarding PAD stage, 52% were stage IIB, 28% stage III, and 19% stage IV. Among the patients, 45% ( n  = 85) had had a previous groin incision. Bacterial swabs were performed in each case of suspected SSI (22.8% [43/188]), while 76.7% (33/188) were negative, there were 5% [5/98] positive swabs in the intervention group and 5.5% [5/90] in the control group). Antibiotics were given to 13.2% of the intervention group, and 31.1% of the control group ( p  = .004). The control group experienced more frequent SSIs (33.3%; 30/90) than the intervention group (13.2%; 13/98; p  = .0015; absolute risk difference −20.1 per 100; 95% CI -31.9 to 8.2). This difference was based on an increased rate of Szilagyi I SSI in the control group (24.6% vs. 8.1%, p  = .0012). Conclusion: The results confirmed a reduced superficial SSI rate after vascular surgical groin incision using ciNPT compared with standard wound dressings.